Comparative phytochemical analysis of the aerial parts of Empetrum nigrum L. samples, collected in various regions of the Russian Federation - A. O. Ponkratova; A. K. Whaley; E. V. Zhokhova; E. A. Bezverkhniaia; V. G. Luzhanin (Разработка и регистрация лекарственных средств)
Introduction. A number of studies have shown that various genetic and environmental factors can affect the biosynthesis and accumulation of secondary metabolites. In particular, it is known that the local geoclimate, seasonal changes, external conditions such as light, temperature, moisture and soil fertility can affect the chemical composition and, as a result, the therapeutic properties of plants used in the pharmaceutical and food industries. Empetrum nigrum L. is a rich source of various pharmacologically active secondary metabolites – chalcones, dihydrochalcones, bibenzyls, 9,10-dihydrophenanthrenes, flavonoids, and proanthocyanidins. In the scientific literature, there is no data on the variation in the chemical composition of E. nigrum depending on the growing area. The obtained data are necessary for a reasonable choice of the collecting location for the plant, with the aim of its further chemical and pharmacological research for the development of promising drug candidates.Aim. To carry out a comparative analysis of secondary metabolites composition in the aerial parts of Empetrum nigrum growing in different regions of the Russian Federation.Materials and methods. Samples collected in three different areas were used to compare HPLC profiles: sample 1 was collected next to SPCPU nursery garden of medicinal plants (Leningrad region, Vsevolozhsky district, Priozerskoe highway, 38 km) in July 2020, sample 2 was collected on the Kola Peninsula, around the Khibiny mountains in July 2020, sample 3 was collected on the Kamchatka Peninsula, next to Khalaktyrsky beach (Pacific Ocean coast) in July 2020. Extracts were analyzed by analytical high performance liquid chromatography (HPLC) using a Prominence LC-20 device (Shimadzu, Japan) equipped with a diode array detector.Results and discussion. As a result of the research, for the first time, a significant variation in the qualitative chemical composition in the aerial parts of Empetrum nigrum growing in different regions of Russian Federation was established. Sample 3, collected on the Kamchatka Peninsula, in comparison with samples 1 and 2, contain the greatest variety of polar secondary metabolites belonging to the classes of flavonoids, tannins, and phenol carboxylic acids, while in the shoots collected in the Leningrad region, the major metabolites were weakly polar compounds belonging to the classes of chalcones, dihydrochalcones, bibenzyls, and 9,10-dihydrophenanthrenes, and in sample 2, collected in the Khibiny mountains, the lowest qualitative content of secondary metabolites was found. This variation may be caused by various environmental factors (biotic and abiotic).Conclusion. For the first time, the comparison of HPLC profiles of aerial part samples of E. nigrum, collected in different regions of the Russia Federation has been carried out. As a result, significant variations in the secondary metabolites composition of the studied samples were established, depending on the regions and growing conditions of the plants. The data obtained can be used for a reasonable choice of the collection location for the plant, with the aim of its further chemical and pharmacological research for the development of promising drug candidates.